Aristotle Talks About the Behavioral Theory of "Accidental Combinations" - Zhang, Yunfeng (Transactions on Social Science, Education and Humanities Research, 2024)
Aristotle raised a profound question in the first paragraph of Z6 in Metaphysics: Is the Accidental combinations the same as what it is? W.D.Ross and Nie Minli have given different explanations about the argumentation process of this paragraph. This paper attempts to restore the content of this paragraph and explain the differences between them. At the same time, it expounds how Aristotle understands the problem of " Accidental combinations " from a broader perspective, and points out that this is related to the evolution of Aristotle’s ontological thought on the relationship between nature and parity, which is by no means an answer like an universal affirmative proposition. Aristotle is actually doubtful about this issue, and Ross’s suspicion of Z6 has its value.